2004
DOI: 10.1016/s0014-5793(04)00383-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a novel Rho GTPase activating protein implicated in receptor-mediated endocytosis

Abstract: Cbl-interacting protein of 85 kDa (CIN85) is a recently identified adaptor protein involved in the endocytic process of several receptor tyrosine kinases. Here we have identified a novel RhoGAP, CIN85 associated multi-domain containing RhoGAP1 (CAMGAP1) as a binding protein for CIN85. CAMGAP1 is composed of an Src homology 3 (SH3) domain, multiple WW domains, a proline-rich region, a PH domain and a RhoGAP domain, and has the domain architecture similar to ARHGAP9 and ARHGAP12. CAMGAP1 mRNA is widely distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…We identified this protein independently as SH3 domain kinase binding-protein 1 (SH3KBP1) and reported that its gene maps to the human X chromosome region p22.1 -p21.3 [2]. CIN85 and its rat homolog, Ruk/SETA [3,4], are widely expressed in a variety of tissues and form complexes with many signaling proteins via its PRR [3][4][5][6][7] or SH3 domains [8][9][10][11]. These complexes play a role in various biological functions, including control of receptor tyrosine kinase (RTK) signaling [6,7,10 -12], rearrangement of the actin cytoskeleton [13], and apoptosis in neuronal cells [3,14].…”
Section: Introductionmentioning
confidence: 99%
“…We identified this protein independently as SH3 domain kinase binding-protein 1 (SH3KBP1) and reported that its gene maps to the human X chromosome region p22.1 -p21.3 [2]. CIN85 and its rat homolog, Ruk/SETA [3,4], are widely expressed in a variety of tissues and form complexes with many signaling proteins via its PRR [3][4][5][6][7] or SH3 domains [8][9][10][11]. These complexes play a role in various biological functions, including control of receptor tyrosine kinase (RTK) signaling [6,7,10 -12], rearrangement of the actin cytoskeleton [13], and apoptosis in neuronal cells [3,14].…”
Section: Introductionmentioning
confidence: 99%